Phylogeny of the genus Austinixa Heard & Manning, 1997, inferred from mitochondrial and nuclear molecular markers, with descriptions of three new species and redescription of Austinixa felipensis (Glassell, 1935) (Decapoda: Brachyura: Pinnotheridae) - Theil, Emma Palacios; Felder, Darryl L. (Zootaxa, 2020)
We used the mitochondrial 16S–NADH1 complex, mitochondrial 12S, and nuclear histone 3 genes to examine evolutionary relationships among members of the genus Austinixa Heard & Manning, 1997, and their relationships to other pinnotherids. The monophyly of Austinixa was confirmed by maximum likelihood, Bayesian, and maximum parsimony analyses. Clades recovered on the basis of molecular data agreed with current morphology-based taxonomy at species rank. Morphological characters presently used to distinguish species of Austinixa are not synapomorphic at higher levels and therefore cannot be used to infer cladistic relationships among them. High genetic and morphological intraspecific variation was observed, consistent with patterns of restricted gene flow likely attributable to climatic and geographic history, physical characteristics of contemporary habitats, and host-related constraints on the symbiotic life styles of Austinixa spp. Molecular and morphological characters warrant description of three new species, herein named and illustrated: Austinixa cuestai sp. nov., from Pacific waters of Panama and Nicaragua; Austinixa artankeri sp. nov., from the Caribbean waters of Panama, Colombia, and Venezuela; and Austinixa roblesi sp. nov., from Belize and Panama. All three species inhabit intertidal zones, as do their congeners. To facilitate comparisons and augment the very limited original description, a redescription of the Pacific species Austinixa felipensis (Glassell, 1935) is provided on the basis of paratypes labelled by Glassell and more recently collected topoptypic specimens.